PEMANFAATAN INFORMATION AND COMMUNICATIONS TECHNOLOGY SEBAGAI SUMBER BELAJAR DI ERA DIGITAL - Erwin, Yolin; Arafat, Yasir; Wardiah, Dessy (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2021)
The purpose of this research is to illustrate that ICT can be used as a source of learning that is very relevant in the digital age. The research method used is a qualitative research method with the type of literature study. The results obtained from research conducted that ICT has many impacts in the development of the learning process. Impacts generated by ICT are not only positive, but also negative impacts. However, in this research that was studied was one of the positive impacts of ICT, which was to become a source of learning in the digital age. Utilization of ICT in learning can optimize lifelong learning through distance and asynchronous mode where students can communicate independently at different times whenever they are online, as well as close the professional isolation space that has often been felt in learning.